The formation of digital business factors - Pyrog, O.; Poritska, A. (Видавництво Львівської політехніки, 2020)
The article is concerned with identifying and studying factors affecting digital business formation and development process in order to form tools for affecting the digital business. The novelty of this research paper is establishing causes increasing the volume of digital business and the dependence of its growth rate on the existing factors. The authors define the concept of digital business as an entrepreneur activity (providing electronic commerce, electronic services) in the Internet for making a profit with the help of information and communication technologies that blur boundaries between the real and virtual worlds. The digital business structure is studied and analysed. It is generally distinguished 4 sectors (electronic financial services; electronic commerce; electronic education and training; other electronic transactions). The authors prove that modern digital business model has been transformed from a 4-sectoral into a 3- sectoral one, including electronic commerce, electronic financial services, electronic education and training. It is suggested to study and define factors affecting the development of digital business according to sevenstage sequence of digital business evaluation. The hypothesis concerning a set of digital business factors is proposed and 24 factors affecting digital business are identified, among which 8 factors mostly affect the digital business market of the European Union. The authors also distinguish influencing factors which are common for all three sectors of digital business, such as: Internet use by individuals, proportion of people using the Internet to order goods or services, the level of household Internet access. The methodology of the given research is based on scientific and verification principles, comparative, structural and system analysis. Applying economic and mathematical methods, it has been investigated the correlation between the digital business and the main factors affecting it. The correlation density between the outcome feature and influencing factors using a determination coefficient is estimated. The given research proves that factors are multicollinear between each other. It has been revealed the correlation between the EU digital business volume and chosen factors
Keywords: digital business; electronic business; electronic commerce; electronic banking; electronic education and training; digital business factors; F10; F17; F20; 339.5; 330.23